Satisfação do cliente: proposta de instrumento de mensuração e diagnóstico da satisfação para a Inviolável Monitoramento Santa Catarina - Battisti, Amanda (2018)
Meeting customer needs is one of the core objectives of a company and keeping them satisfied is a daily challenge for any company that wants to gain and sustain long-term competitive advantage. Offering a quality product or service is no longer enough, what customers want is to have their expectations surpassed. The relationship between expectations and satisfaction occurs as satisfaction is defined as the result of the difference between customer expectations and perceptions about a product or service. Thus, diagnosing and monitoring customer satisfaction is a fundamental task for the management of companies, because their understanding provides an evaluation of performance and assists in the creation and delivery of superior value added. However, because of the particularities of services, measuring satisfaction can become a complex activity. In this sense, the present work aims to diagnose the satisfaction of the clients of the company Inviolável Santa Catarina Monitoring, based on measurement metrics in the marketing literature. In addition to the diagnosis, this study proposes an instrument for measuring satisfaction, specific and according to the particularities of the private security services sector. For that, a case study with a qualitative and exploratory approach was carried out. In the scope of the study, the SERVQUAL metric was used to base the elaboration of the qualitative instrument. In view of the diagnosis made, it was possible to verify that the clients value more the dimensions that are directly related to the provision of the service and in relation to the private security service, reliability is the paramount element highlighted. SERVQUAL proposes that the perceived quality is the result of the difference between the perceptions and expectations about the service, ie, P - E = Q. On the results found, the expectations and perceptions pointed out show that, in general, there is quality in the services provided by the Company and customers are satisfied.